216k views
5 votes
Given: F=(0,1),(2,4),(4,6),(6,8) and g=(2,5),(4,7),(5,8),(6,9),(7,5) (fxg)(2)

User Hmatar
by
4.7k points

2 Answers

4 votes

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️


f * g = (2 \: , \:4 * 5) \: , \: (4 \: , \: 6 * 7) \: , \: (6 \: , \: 8 * 9) \\


f * g = (2 \: , \: 20) \: , \: (4 \: , \: 42) \: , \: (6 \: , \: 72) \\

_________________________________

Thus ;


(f * g)(2) = 20

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

User IkePr
by
5.7k points
5 votes

Answer:

(F-G)(x) = -1

Step-by-step explanation:

The notation (F - G)(x) means to subtract each function when x = 6. According to the sets when x = 6 then F is (6,8) and G is (6,9). To subtract the functions, subtract their output values. (F-G)(x) = 8 - 9 = -1.

Explanation:

User Bensw
by
4.1k points